Interlanguage Analysis on Indonesian EFL Learners’ Compositions - Maheswari, Putu Ayu Masita; Adnyani, Ni Luh Putu Sri; Suwastini, Ni Komang Arie (English Department FBS UNP, 2020)
This study aims at investigating the interlanguage production by Indonesian EFL students in their English compositions. Interlanguage describes the language produced by second or foreign language learners when learning the target language. Forty college students majoring in English for tourism industry were the subjects in this study. In collecting the data, the students were asked to write a recount text with a topic